The implication of the shortage of health workforce specialist on universal health coverage in Kenya - Mumbo Hazel Miseda; Samuel Odhiambo Were; Cirindi Anne Murianki; Milo Peter Mutuku; Stephen N. Mutwiwa (BMC, 2017)
Abstract Background Globally, there is an acute shortage of human resources for health (HRH), and the greatest burden is borne by low-income countries especially in sub-Saharan Africa and some parts of Asia. This shortage has not only considerably constrained the achievement of health-related development goals but also impeded accelerated progress towards universal health coverage (UHC). Like any other low-income country, Kenya is experiencing health workforce shortage particularly in specialized healthcare workers to cater for the rapidly growing need for specialized health care (MOH Training Needs Assessment report (2015)). Efficient use of the existing health workforce including task shifting is under consideration as a short-term stop gap measure while deliberate efforts are being put on retention policies and increased production of HRH. Methods The Ministry of Health (MOH) with support from the United States Agency for International Development-funded FUNZOKenya project and MOH/Japan International Cooperation Agency (JICA) project conducted a country-wide training needs assessment (TNA) to identify skill gaps in the provision of specialized health care in private and public hospitals in 46 out of Kenya's 47 counties between April and June 2015. A total of 99 respondents participated in the TNA. Structured questionnaires were used to undertake this assessment. The assessment sought to determine the extent of skill gaps on the basis of the national guidelines and as perceived by the County Directors of Health (CDH). The questionnaires were posted to and received by all the respondents a week prior to a face-to-face interview with the respondents for familiarization. Data analysis was done using SPSS statistical package. Results Overall, the findings revealed average skill gaps on selected specialists (healthcare professional whose practice is limited to a particular area, such as a branch of medicine, surgery, or nursing, especially, one who by virtue of advanced training is certified by a specialty board as being qualified to so limit his or her practice, Free dictionary) at 85 and 62% when compared to the guideline and as perceived by the CDH respectively. It also revealed that gynecologists exceeded the requirements by 88 and 246% against the guidelines and as perceived by the CDH respectively. Conclusion There is an overall huge gap in health specialists across the 46 counties, and the focus of training should be on the following specialists: cardio-surgeons, neurosurgeons, oncologists, nephrologists, lung and skin clinical officers, anesthetic clinical officers, cardiology nurses, forensic nurses, dental nurses, accident and emergency nurses, and oncology nurses. More innovative approaches, including the use of technology, need to be considered to address this challenge in the immediate, medium, and long terms. Policies and legal frameworks should be developed to facilitate cross-county sharing of specialist expertise. Efforts need to be made to ensure harmonized skill gaps revealed by the guideline and as perceived by the CDHs to inform the development of mitigation strategies.